Chaos als neues naturwissenschafliches Paradigma - Rojas, Raul (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1992)
Tue author describes the theory of chaos as a scientific revolution which reaches beyond the microphysical indeterminism of Quantum Mechanics by abolishing determinism also on the macroscopical level. With a simple non-linear system the notions bifurcation, strange attractor, universality of chaos, self-organization and criticality are explained and illustrated through examples.